2018
DOI: 10.1002/ecs2.2135
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of amino acid supply in mesozooplankton during cyanobacteria blooms: a stable nitrogen isotope approach

Abstract: Knowledge of how zooplankton can utilize cyanobacteria to sustain their nitrogen (N) demand for essential compounds like amino acids (AAs) is a key to predicting responses of higher trophic levels in terms of production and food web structure to future enhanced water column stratification. We explored the natural abundances of bulk N and AA‐specific nitrogen isotopes (δ15N) in particulate organic matter and mesozooplankton size‐fraction samples from three vertically separated water bodies in the central Baltic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 68 publications
(204 reference statements)
2
45
0
Order By: Relevance
“…Moreover, in a complementary study by Eglite et al (2018) it was shown that the total phytoplankton cell-C concentrations decreased with depth that could not only be a result from light limitation but additionally from feeding pressure by abundant mesozooplankton.…”
Section: Foraging Strategies Of Key Copepod Speciesmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, in a complementary study by Eglite et al (2018) it was shown that the total phytoplankton cell-C concentrations decreased with depth that could not only be a result from light limitation but additionally from feeding pressure by abundant mesozooplankton.…”
Section: Foraging Strategies Of Key Copepod Speciesmentioning
confidence: 99%
“…The temperature program was used as described in Eglite et al (2018). The combustion unit was a Thermo IsoLink fixed at the GC oven and connected to the IRMS via a ConFlo IV interface.…”
Section: Bulk and Compound-specific Stable Isotope Analysesmentioning
confidence: 99%
See 3 more Smart Citations